Senofane DK 21 B 18 sullo sfondo della cultura milesia - Beconi, Marco (Peitho. Examina Antiqua, 2024)
In this paper, I will first try to refute Lesher’s hypothesis who reads in 18.1 a polemical reference to divination: in the first verse, in fact, Xenophanes merely outlines an exemplum fictum, punctually overturned in 18.2. The fragment must be read, on the contrary, against the historical background that produced it. The language of Xenophanes in B18 is the same as ever and many are the interconnections with the remaining evidences. Here it is enough to recall the link with the two surviving elegies, in which the value of intellectuals is proudly claimed, as opposed to that of the athletes hailed by the masses. It will come as no surprise, therefore, that in B18 the researchers (ζητοῦντες) are celebrated, with a genuine ‘monument’ to what was being discovered at Miletus. I will also try to show how previous interpretations have been vitiated by an unfair devaluation of Xenophanes’ ‘scientific’ activity, seen as a pre-Herodotean ἱστορίη, not as an investigation referring to a methodology that was taking shape and in which Xenophanes largely recognised himself. B18, therefore, is not the first affirmation of coherent ‘philosophical’ interpretation, but the first, brilliant intuition of what enquiry was revealing, in opposition to the mythical tradition, in a passage from μῦθος to λόγος that was gradual, rich in nuances, but irreversible.